I slay, okay how mediated race in Western pop music videos affect a Filipina's self-concept - De Leon, Angelica Linda Leonila A. 1997-; Feliciano, Rosa Maria T.; University of the Philippines Diliman. College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2018)
This thesis examines the effects of mediated race on morena Filipinas. Specifically, it looks at how Beyonce affects the self-concept of her morena Filipina fans, thus posing the question: how does the representation of Beyonce's body in her album Lemonade affect and represent the self-concept of her morena Filipina fans? The researcher believes that representations of Beyonce's body have the capacity to influence the ideal image of a person's self-concept, which is why the researcher wants to determine whether its effects lead to a congruent or incongruent self-actualization. Using Carl Rogers' three components of the Self-Concept Theory, supplemented by the Representation Theory, Self-Objectification Theory and the Critical Race Theory, the thesis utilizes a thematic analysis on ten screenshots from Beyonce's Lemonade, and the fifteen online interviews with 18-25 year old members of the Beyonce Philippine Facebook group. The interviews are structured into three parts in order to discover each participant's self-image, idealized self, and perceived self-esteem. Furthermore, the study intends to take a critical look at the findings with some postcolonial analysis.
Vita.
Thesis (A. B. Broadcast Communication)--University of the Philippines Diliman
Includes bibliographical references.
Keywords: Women -- Philippines; Self-perception -- Philippines